Prevalence and sociodemographic determinants of the Gulliver syndrome in 395,660 Spanish workers - Mónica Moreno-Martínez; Pedro Juan Tárraga-López; José Ignacio Ramírez-Manent; María Teófila Vicente-Herrero; Mónica Silu Piña-Abreu; Ángel Arturo López-González (Academic Journal of Health Sciences, 2026)
Background: The Gulliver syndrome is a recently proposed conceptual framework intended to identify individuals with the simultaneous presence of multiple borderline cardiometabolic abnormalities that, when considered separately, may appear clinically unimportant. However, its epidemiological characteristics and sociodemographic distribution remain unknown. This study aimed to estimate, for the first time, the prevalence of Gulliver syndrome and to examine its association with sex, age, social class, and educational attainment in a large cohort of Spanish workers. Methods: A cross-sectional study was conducted among 395,660 Spanish workers undergoing routine occupational health examinations between 2019 and 2020. Gulliver syndrome was defined as the simultaneous presence of borderline abdominal adiposity, prehypertensive blood pressure, impaired fasting glucose, and elevated non-high-density lipoprotein cholesterol according to previously proposed criteria. Crude prevalence estimates and multivariable logistic regression analyses were performed to identify independent sociodemographic determinants associated with the syndrome. Results: A total of 10,920 workers fulfilled the diagnostic criteria for Gulliver syndrome, corresponding to an overall prevalence of 2.76% (95% confidence interval [CI]: 2.71–2.81). The prevalence was markedly higher in men than in women (3.83% vs. 1.11%, p